A meta-analysis on sleep quality in inflammatory bowel disease. (December 2021) - Ballesio, Andrea; Zagaria, Andrea; Baccini, Flavia; Micheli, Federica; Di Nardo, Giovanni; Lombardo, Caterina
Summary: Evidence of poor sleep quality in inflammatory bowel disease (IBD, i.e., Crohn's disease and ulcerative colitis) has been reported but never systematically reviewed or meta-analysed. We conducted a systematic review and meta-analysis of pairwise comparisons that included 1) IBD patients/controls, 2) Crohn's disease/ulcerative colitis, 3) active/inactive IBD on standardised measures of sleep quality. PubMed, Medline, PsycINFO, Scopus, and CINAHL were searched up to March 2021. Forty-two studies met the inclusion criteria. Results showed poorer subjective sleep quality in IBD patients than in controls, with moderate effect sizes (g = .49, [95% CI = .32 - .66], p < .001). No differences within IBD subtypes were found (g = −.07, [95% CI = −.17–.05], p = .208). Individuals with an active IBD reported poorer sleep quality than those in remission, with a large effect size (g = .66, [95% CI = .35 - .98], p < .001). Results on objectively recorded sleep were mixed, with no clear evidence of objective sleep impairments in individuals with IBD. Results support the view of subjective poor sleep quality as a relevant comorbidity in IBD. As a potential factor affecting immune and inflammatory responses as well as patients' quality of life, sleep quality should be taken into account in the treatment of IBD.